2017
DOI: 10.22630/prs.2017.17.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Konkurencyjność kosztowa gospodarstw ogrodniczych w Polsce i wybranych krajach UE

Abstract: In the conditions of growing globalization and export-oriented nature of the Polish horticulture systematic studies of the competitive position of horticultural businesses are necessary, including cost competitiveness. The paper presents the vertical and horizontal analysis of the costs in horticultural farms in six EU countries, the largest fruit and vegetable producers. It has been shown that Poland still has a favorable competitive position in terms of costs, but their relatively fast growth and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A comparison of the dynamics of changes in the area of crops and harvest shows that in most countries (except France and Italy) there was an increase in productivity per area unit. It should be emphasized that in the case of Poland, the indicated increase in production (changes in the cultivated area are particularly visible in Poland in the 2004-2008and particularly visible in Poland in the 2004-2008and articularly visible in Poland in the 2004-2008and 2009 does not confirm the results of previous research, which showed a clear decrease in the area of crops and harvest after 2004 [Olewnicki 2011, Jabłońska et al 2017]. This discrepancy results from the fact that the Eurostat data used in this paper and the data of the Statistics Poland, used in the above publications are clearly different.…”
Section: Production �O��um� �Nd ���R��� Cu��ti��tion �R��mentioning
confidence: 59%
“…A comparison of the dynamics of changes in the area of crops and harvest shows that in most countries (except France and Italy) there was an increase in productivity per area unit. It should be emphasized that in the case of Poland, the indicated increase in production (changes in the cultivated area are particularly visible in Poland in the 2004-2008and particularly visible in Poland in the 2004-2008and articularly visible in Poland in the 2004-2008and 2009 does not confirm the results of previous research, which showed a clear decrease in the area of crops and harvest after 2004 [Olewnicki 2011, Jabłońska et al 2017]. This discrepancy results from the fact that the Eurostat data used in this paper and the data of the Statistics Poland, used in the above publications are clearly different.…”
Section: Production �O��um� �Nd ���R��� Cu��ti��tion �R��mentioning
confidence: 59%
“…The high quality of Polish raspberry fruit is a result of a combination of relatively favorable climatic and soil conditions as well as advanced technologies. As stressed by Jabłońska et al (2017), in Poland the issue of external competition in raspberry production, which is definitely export-oriented, appears of the utmost importance. For many years Poland and Serbia have played the dominating roles in European raspberry production for processing purposes.…”
Section: Introductionmentioning
confidence: 99%